Moving in the Spirit: Called to Transforming Discipleship. (November 2016) - Robra, Martin
Abstract: Together towards Life (TTL) holds together a theology of the God of life and the transforming power of the Holy Spirit with the renewal and transformation that begins with a commitment to justice and peace at the margins and anticipates the eschatological vision of the renewal of the whole creation. The theme of the forthcoming World Mission Conference in 2017 in Arusha (Tanzania), "Moving in the Spirit: Called to Transforming Discipleship, " marks the intersection between TTL and the Busan call for the pilgrimage of justice and peace. The theme invites participants to advance reflection on the life‐giving power of the Holy Spirit and the role of transformative communities moving together in hope of God's reign to come. The example of the World Council of Churches' work on a Theology of Life shows that choosing this direction has implications for the practices of doing theology and even the organization of the forthcoming World Mission Conference. A fascinating task indeed!